MOTIVATION OF INDEPENDENT LEARNING ACTIVITY OF STUDENTS OF HIGHER TECHNICAL EDUCATIONAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2008)
The main aspects and points of professional motivation of the technical university students’ self-work are determined in this article. The lecturer’s functions within students’ self-work, are de fined.
Keywords: self-work; motivation; readiness for professional activity